Pub Culture: State Authority and Alternate Religiosity in Indonesian Pesisir - Zahra, Fathimatuz (DINIKA : Academic Journal of Islamic Studies, 2017)
The image changing of Pati from a religious city to a pub culture city has ensued for fifteen years. Thus, the efforts of restoring the condition will not be easy. Previously, the pubs were used as family pubs. However, nowadays, the number of the pubs has increased. Violence was often used by some religious organizations to solve the problem. Nevertheless, this effort did not give any significant effects. In this article, the religiosity of pub culture is formulized. The result of this study is expected to be one of the concrete solutions for restoring the image of Pati.Â KeywordsReligiosity, Pub-culture, Culture